Comparison of Hiraoka's Transurethral Detachment Prostatectomy and Transurethral Resection of the Prostate Effects on Postoperative Erectile Function in Patients with Benign Prostatic Hyperplasia: A Prospective Randomized Controlled Study. Issue 11 (11th July 2020) - Pan, Chunyu; Zhan, Yunhong; Zhao, Yueyang; Wu, Bin; Bai, Song
Abstract: Background: Currently, no study has focused on the postoperative erectile function in patients with benign prostatic hyperplasia (BPH) by comparing Hiraoka's transurethral detachment of prostate (TUDP) and transurethral resection of prostate (TURP). Aim: To compare the effects of Hiraoka's TUDP and TURP on postoperative erectile function in patients with BPH after long-term follow-up. Methods: A total of 104 consecutive patients with BPH treated in our hospital between September 2018 and February 2019 were included in the study. All patients who met the inclusion criteria were randomly divided into the Hiraoka's TUDP (n = 52) and TURP (n = 52) groups. Patient baseline data were collected. The international index of erectile function (IIEF-5), minimal clinically important difference (MCID), and quality of life scale (QOLS) were used to evaluate erectile function and quality of life 3, 6, and 12 months after surgery. Primary study endpoints were IIEF-5 and MCID. Secondary study endpoints were QOLS and independent prognostic factors for MCID. Outcomes: Hiraoka's TUDP experienced greater improvement in postoperative IIEF5 scores than patients who underwent TURP. Results: Patients in the Hiraoka's TUDP group had significantly higher mean IIEF-5 scores than those in the TURP group 6 and 12 months after surgery (6 months: 18.9 vs 14.8, P < .001; 12 months: 18.1 vs 15.7, P < .001). The percentages of patients in the TUDP group who achieved an MCID were 88.5% and 80.8%, compared to 30.8% and 46.2% in the TURP group ( P < .001 for both), 6 and 12 months after the operation, respectively. Patients in the TUDP group had lower QOLS scores than those in the TURP group after the surgery. The surgical method was an independent prognostic factor for MCID (odds ratio = 0.218). Clinical Implications: Until now, no study has focused on the postoperative erectile function in patients with BPH by comparing Hiraoka's TUDP and TURP. Our study addressed this issue, which can add a new paradigm in the management to BPH. Strength & Limitations: The comparison between Hiraoka's TUDP and TURP using a statistically appropriate, adequately powered methodology is the strength of the study. The single center and less participants are the limitations of the study. We believe that multicenter and large-sample studies are needed to further verify these study conclusions. Conclusions: Among similar cohorts of patients with BPH who underwent TUDP and TURP, patients who underwent Hiraoka's TUDP experienced greater improvement in postoperative IIEF5 scores than patients who underwent TURP, while improvement in IPSS was similar among both groups.